PENGARUH ISLAMIC BRANDING DAN PERILAKU RELIGIUS TERHADAP KEPUASAN NASABAH PADA BSM PALU - Khairunnisa, Gina; Zahara, Zakiyah (Universitas Tadulako, 2021)
This study aims to analyze the influence of Islamic branding and religious behavior on customer satisfaction Bank Syariah Mandiri Palu. The research method used is a causal descriptive method with a sample of 60 people. The form of sampling in this study is non-probability with a purposive sampling technique. The analytical method used in this study is Partial Least Square (PLS) with the help of the SmartPLS 3.0 statistical program. The results showed that Islamic branding had a significant effect on customer satisfaction of Bank Syariah Mandiri Palu while religious behavior did not significantly influence customer satisfaction at Bank Syariah Mandiri Palu.